Prognostic Significance of Premature Ventricular Contractions without Obvious Heart Diseases Determined by Standard 12‐Lead Electrocardiography Considering their Morphology. Issue 2 (17th April 2015) - Haruta, Daisuke; Akahoshi, Masazumi; Hida, Ayumi; Sera, Nobuko; Imaizumi, Misa; Ichimaru, Shinichiro; Nakashima, Eiji; Takahashi, Ikuno; Ohishi, Waka; Fukae, Satoki; Maemura, Koji
Abstract : Background: Although ventricular premature contraction (VPC) commonly arises in subjects with and without heart diseases, the prognosis of VPC has remained controversial and the effect of their morphology on mortality has not been fully determined in subjects without obvious heart diseases. The objective of this study was to assess the morphologic effect of VPC on mortality. Methods: Japanese atomic bomb survivors (n = 6685) underwent baseline health examinations and standard 12‐lead electrocardiogram (ECG) between January 1990 and December 1991. Of these, we extracted data from 5, 685 (67.1% women) subjects who had neither heart diseases nor electrocardiographic abnormalities at baseline. Among them, we identified 131 VPC cases using standard 12‐lead ECG and classified them into left bundle branch block (LBBB) type (n = 74), right bundle branch block (RBBB) type (n = 21), and undetermined type (n = 36) according to their morphology. These subjects were followed up until December 2008; we compared all‐cause, cardiac and coronary heart disease (CHD) mortality rates using multivariate Cox regression analysis between those with and without VPC. Results: No VPCs were associated with all‐cause and cardiac mortality, but the LBBB type was significantly associated with CHD mortality (hazard ratio, 2.73; 95% confidence interval, 1.11–6.73) after controlling for age, sex, smoking status, alcohol consumption, and underlying diseases. Conclusions: Among Japanese atomic bomb survivors without obvious heart diseases, LBBB‐type VPC was associated with increased CHD mortality. Larger studies are needed to confirm the effect of morphology as it might help to predict the risk.